(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2026)
Metformin, the main drug for the treatment of type 2 diabetes mellitus, has a multifaceted mechanism of action, which includes inhibition of gluconeogenesis in the liver and increased peripheral glucose uptake and tissue sensitivity to insulin. The compound also has antioxidant and cardioprotective properties, reducing the risk of cardiovascular complications in diabetes. Accumulated data indicate its potential in cancer prevention and therapy, and metformin is a promising multifunctional agent for the comprehensive treatment of type 2 diabetes mellitus.